Learning vocabulary through songs: A study on the role of music in teaching verbs - Md Zamin, Ainul Azmin; Adzmi, Nor Azrul Hardi; Mohamad, Maslawati (2020)
Purpose of the study: This study aims to investigate how the use of songs in English language classrooms could aid tertiary students to increase their verb vocabulary repertoire. Methodology: This quantitative study was carried out among diploma students from a local university in Malaysia. The students were exposed to various English songs during their English lessons. Pre-test and post-test were conducted in this study. Main Findings: The use of songs can increase vocabulary acquisition among English language learners at tertiary level. The use of songs is able to provide a fun way of picking up new words. Applications of this study: The findings of this research indicate that English language teachers of tertiary students should use English songs as classroom activities to facilitate their students’ language learning and motivate them in acquiring new English vocabulary. The findings of this research are useful for university policymakers, teachers, and students. Novelty/Originality of this study: In this research, the use of English songs from contemporary genres, such as Western or Islamic songs can be an effective way to promote language learning.